Enhancing the RECTANGLE Algorithm for Text Data Encryption in Mobile Applications Utilizing BBSXOR, NonceXOR, and Modulo Addition - Velarde, Karylle Andrei C.; Enciso, Raphael P.; Agustin, Vivien A.; Morano, Jonathan C.; Mahusay, Leisyl M.; Guialil, Jamillah S. (International Journal of Computing Sciences Research; Vol 8 (2024): Volume 8, 2024)
Purpose –This study proposes enhancing the RECTANGLE algorithm by addressing its problems and security by modifying its key schedule and encryption algorithm. Method –To enhance the Key Schedule Algorithm, the researchers have chosen a CSPRNG, the BlumBlumShub. For the Encryption Algorithm, researchers chose to incorporate ModuloAddition and NonceXOR into the algorithm. Results –The proposed enhancement was compared with existing algorithms across three tests: Frequency, Correlation Coefficient, and Avalanche Effect. The Proposed Enhancement excelled, achieving a 96% success rate in the Frequency Test, fewer moderate positive relationships in the Correlation Coefficient, and surpassing the 50% threshold in the Avalanche Effect Test with a 55% avalanche effect result. Conclusion – This study significantly enhances the RECTANGLE algorithm through targeted modifications on its key schedule and encryption algorithm. Tests and analysis show that it effectively addresses known weaknesses, resulting in improved security properties. Recommendations – Further work on refining the modifications made to the algorithm is recommended to mitigate any potential performance degradation observed in the study. Research Implications – The enhanced RECTANGLE Algorithm showcases notable advancements in randomness, key generation, and confusion properties, enhancing its security and efficacy in encryption tasks. Despite minor performance impacts from modifications, its overall robustness in lightweight block cipher algorithms highlights the importance of continual refinement to meet evolving security standards.